Mgmt - Williams, Chuck (Mason, OH : Cengage Learning, 2014)
Provides a concepts-driven format with optional exercises, cases, and practical applications that you can choose to use depending on your students' needs. This title allows you to manage the subtle dynamics of teaching Principles of Management, with problem sets that guide students through a lower and higher order thinking skills exercises.
PART I: INTRODUCTION TO MANAGEMENT. 1. Management. 2. History of Management. 3. Organizational Environments and Cultures. 4. Ethics and Social Responsibility. PART II: PLANNING. 5. Planning and Decision Making. 6. Organizational Strategy. 7. Innovation and Change. 8. Global Management. PART III: ORGANIZING. 9. Designing Adaptive Organizations. 10. Managing Teams. 11. Managing Human Resource Systems. 12. Managing Individuals and a Diverse Work Force. PART IV: LEADING. 13. Motivation. 14. Leadership. 15. Managing Communication. PART V: CONTROLLING. 16. Control. 17. Managing Information. 18. Managing Service and Manufacturing Operations. Endnotes. Name Index. Subject Index.
Includes bibliographical references and index.
Keywords: Administration; Management; Planning